Unitary perturbation theory applied to multiconfigurational reference functions. Issue 3 (18th April 2012) - Nagy, Péter R.; Szabados, Ágnes; Nakai, Hiromi; Yoshizawa, Kazunari; Ando, Koji; Nakajima, Takahito; Brändas, Erkki J.
Abstract Unitary parametrization of the wave operator in the form suggested by Mayer is studied in the multireference framework. The investigated unitary perturbation theory (UPT) constructs a first correction in terms of the functions having nonzero interaction with the reference state via the Hamiltonian. Parameters in the exponential of the wave operator are determined by two dimensional eigenvalue equations. Because of the unitary mapping, UPT is unaffected by the quasi‐degeneracy problem, making it an ideal tool for correcting multireference starting functions. Lack of size‐consistency is however a shortcoming of the method. Applications of UPT as well as the related degeneracy‐corrected PT (DCPT) are presented on intruder prone examples like the symmetric dissociation of the water molecule, the BeH2 system and the two lowest lying states of the scandium dimer. Size consistency violation is analysed and evaluated on the example of the water dimer. Tractability of excited states by UPT is examined by computing the singlet–triplet splitting of the CH2 molecule. © 2012 Wiley Periodicals, Inc.